Education Management in Nigeria: Problems and Solutions - Hussaini Adamu Kankia; Umar Atiku (International Journal on Integrated Education, 2023)
This paper discussed problems facing educational management in Nigeria. Secondary data were used in the paper. The secondary data were gathered from print materials and online publications. The paper concluded that poor funding, inadequate teachers, shortage of infrastructure facilities, instructional materials, appointment of non-professional educationalist, lack of current data, insecurity problem, weak manager, corruption, brand-drain and unstable policies are challenges facing educational management in Nigeria. The paper hereby recommended for increment of education budget, employment of more professional teachers, provision of more infrastructure facilities, instructional materials, current data, and adequate security in schools. The government should appoint competed school managers, deploy human and ICT resources to combat corruption, motivate teachers to prevent brain-drain and ensure stable educational policies.